Correlation of prostate specific antigen level with histopathological findings in patients with prostatic disease - Dr. Panna Shetty; Dr Brij Mohan Kumar Singh; Dr. Tanvi Shetty; Dr. Arijit Bishnu (Tropical Journal of Pathology and Microbiology)
Background: Carcinoma of prostate is one of the common tumors of old age in men. Although there is great apprehension in these patients when they are associated with even mild increase in the prostate specific antigen level (PSA) which can be seen in various benign lesions of prostate. With digital rectal examination (DRE), prostate specific antigen (PSA) remains a major screening tool for early detection of prostate cancer. Materials and method: The study includes 150 cases who presented clinically as prostatic lesions and in whom the PSA levels and tissue biopsy was available and was further correlated among spectrum of prostatic disease. Results: All cases with abnormal DRE were turn out to be malignant lesion on biopsy and was found that the cut off of PSA level for malignancy was 19.5ng/ml. The median PSA levels for benign prostatic hyperplasia (BPH), prostatitis, prostate intraepithelial neoplasia (PIN) and adenocarcinoma is 5ng/ml, 10 ng/ml, 14 ng/ml and 81ng/ml respectively. Statistically there was no significant difference of the PSA levels between low grade prostate intraepithelial neoplasm and high grade. Conclusion: In Benign prostatic lesion, PSA level ranges between 0 to 4.0ng/ml. The cut off value of 19.5ng/ml of PSA is most sensitive and specific for the detection of malignant lesion in the prostate. In addition to elevated level of more than 4.0ng/ml and abnormal DRE with TURP biopsy is most useful and accurate diagnostic method for prostatic lesions. All raised PSA levels cases were not malignant thus it is required to use this biochemical marker judiciously to minimize the apprehension among these patients.